Gnathostomiasis - A Rare Nematode Infection - Rahman, MM (TAJ: Journal of Teachers Association, 2009)
Gnathostoma, primarily an animal nematode, is rusty in colour, 2-3 cm long in adult stage, can infect man by their larval form. Human infection occurs by the third stage larva by consumption of undercooked or raw fish, poultry, or pork and rarely by skin penetration, In Bangladesh gnathostomiasis is not reported. But recently a female of 38 year of age of the northern district, Rangpur has got infected with a species of Gnathostoma, manifested by the appearance of the farva in anterior chamber of her right eye. The larva was removed from her eye surgically in living state and the patient was cured. doi: 10.3329/taj.v16i1.3900 TAJ June 2003; Vol.16(1): 28-29